(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Stealth, mechanical and thermal properties, resistance to fire by limiting oxygen and retarding flame can lead to save several human lifes travelling and working in civil, commercial as well as defence air transport and could even develop drone and aircraft meant to escape enemy countries radar tracing and monitoring range. GFRP play very important role in engineering application. The composite manufactured using nanofillers have found to posses better propeties in certain application. In the present work, MWCNTs, Nanoclay and ZnO have been used in GFRP. The developed material can be a promising replacement of composites being used for structural applications in the aerospace sector and space technology apart from the automotives to impart light weight, superior bending and tensile strength. Testing of GFRP infused nanofillers was conducted to obtain the ultimate tensile strength and flexural bending strength of the composite. Experimental design with three Nanofillers as parameters at three levels for optimization of output characteristics with superior properties for structural applications was done using Taguchi’s L9 and L18 orthogonal arrays. ANOVA Analysis was also performed for both L9 and L18 arrays. The effects of three nanofillers infused GFRP was investigated and their impact on tensile and flexural strength were evaluated.